Regulação da distribuição de gás natural no estado da Bahia - Bezerra, Marcus Vinicius Gomes (2008)
This work is a study about the regulation and the distribution of natural gas in the State of Bahia. With this purpose we drew a comparative one with the regulation done in São Paulo, through his agency CSPE. The natural gas has recent use in the country in relation to the world. That period was marked basically by three moments: The first happens in Bahia, only state to use that product in the supply to the industrial sector. In a second moment, it happened the development of the sector indeed in the country with the discovery of natural gas in Campos' basin, state of Rio de Janeiro. The third party and last moment, it was the great mark of the coming imports of Bolivia, through the gas pipeline Brazil-Bolivia. To leave of that moment a great expansion of the market of natural gas in the country, fact that created need of an effective regulation happened. However, most of the Brazilian states, including Bahia, didn't follow that tendency, having a deficient regulation, introducing many fails. In São Paulo that situation is inverse, the state has a ripe market and developed wide experience in the sector, doing with that he serves as reference for a future regulation of the distribution in Bahia